2011
DOI: 10.1002/cncr.26061
|View full text |Cite
|
Sign up to set email alerts
|

Steroid receptor expression in thymomas and thymic carcinomas

Abstract: BACKGROUND: Although protein expressions of glucocorticoid receptor (GR), estrogen receptors (ERa and ERb), progesterone receptor A (PgR-A), and androgen receptor (AR) were shown to play roles in the growth and differentiation of normal thymus and thymic tumors, to the authors' knowledge their association with patient characteristics and prognosis has yet to be determined. METHODS: A series of 140 thymic epithelial tumors (57 type A þ AB thymomas, 40 type B1 þ B2 thymomas, 6 type B3 thymomas, and 37 thymic car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
(36 reference statements)
1
9
0
2
Order By: Relevance
“…A large number of studies have reported that estrogen is involved in biological functions in human and animal organs through estrogen receptors, including ERα and ERβ (which has at least five isoforms, such as ERβ5) (22)(23)(24). At present, controversial findings exist on the expression of estrogen receptors in thymic tumors, since a number studies reported overexpression of ERβ in these tumors, whereas others studies obtained contradictory results (11,12,13,19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of studies have reported that estrogen is involved in biological functions in human and animal organs through estrogen receptors, including ERα and ERβ (which has at least five isoforms, such as ERβ5) (22)(23)(24). At present, controversial findings exist on the expression of estrogen receptors in thymic tumors, since a number studies reported overexpression of ERβ in these tumors, whereas others studies obtained contradictory results (11,12,13,19).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen has been demonstrated to exhibit pleiotropic effects by binding to intracellular receptors, including estrogen receptors (ER)α and β. Previous meta-analyses observed that ERα was not overexpressed in thymic tumors (including thymomas and thymic carcinomas) compared with in benign thymic tissues, whereas ERβ was overexpressed, which may indicate binding to ERβ and complex estrogen physiological effects (12,13).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, it was also reported to act on both neoplastic thymic epithelial cells and lymphocytes [31]. Glucocorticoid receptor (GR) is expressed in all histological types of thymoma, and no significant difference has been identified among the different subtypes [32]. Furthermore, steroid pulse therapy has been reported to induce the apoptosis of both neoplastic thymic epithelial cells and lymphocytes [15,33].…”
Section: Discussionmentioning
confidence: 99%
“…Un aspecto relevante en el enfrentamiento de las NET, son los significativos avances en biología y patología molecular que recientemente han identificado características moleculares de ellas 6,46,47 . Una caracterización molecular de las NET podría ofrecer estrategias para optimizar el diagnóstico, tratamiento y pronóstico.…”
unclassified